KONFIGURASI SATU PINTU DATABASE PENGHIMPUNAN BANTUAN SEBAGAI MANAJEMEN MITIGASI BENCANA ALAM - Sabariah, Etika (AGUSPATI Research Institute, 2021)
Indonesia is an archipelagic country that has a ring of fire and a blue ring that requires coexistence with natural disasters. The research aims to maintain the pace of economic growth by accelerating the handling of natural disasters through a one-stop configuration of the collection of aid and spending in the natural disaster mitigation room and creating miss zero communication. This type of research is applied through a deductive approach to combined theory to test the usefulness of theory in problem solving on secondary data, previous research and literature studies. Validation and reliability tests are carried out through logical reasoning from a combination of theory and design configuration data. Descriptive analysis (description) of design and descriptive analysis of deductive reasoning combined theory in problem solving space. Deductive descriptive analysis includes: 1) How Integration Works in the scope of resources and human resources and how the data configuration works is information that is part of the resource and 2) the work system and effectiveness becomes a data configuration review to become the basis for social activities. natural disaster mitigation. Descriptive analysis of the design on the configuration data is the process of identification, execution in registers, accounting structures, controls, and audits, focusing on stock cards and investigative audits through monitoring the collection of funds and spending on the configuration design of one data on the number of social activities carried out in dealing with disasters. nature happens